2021
DOI: 10.1542/peds.2020-033134
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Suicidal Behavior and Social Support Among Sexual- and Gender-Minority Youth

Abstract: OBJECTIVES: In this study, we examine reports of exposure to suicidal behavior by youth sexual and gender identity. We explore how exposure is related to depressed mood in the context of high social support while accounting for cumulative adversity.METHODS: Data from a large national sample of youth aged 14 to 15 years in the United States (N = 3979) were collected online in 2018-2019.RESULTS: Sexual-and gender-minority youth were more likely to know someone close to them who attempted suicide, relative to cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
(89 reference statements)
3
4
0
1
Order By: Relevance
“…Older participants (ages 18-23) reported greater exposure, as did participants who listed their race as white, sexual and gender minority participants, and those living in low-income households. These findings are similar to other studies that showed greater exposure among sexual and gender minority youth and among older youth [4,37,50]. Previous research on the risk for SDV finds some differences between younger and older adolescents on factors that increase risk for suicide [51].…”
Section: Discussionsupporting
confidence: 89%
“…Older participants (ages 18-23) reported greater exposure, as did participants who listed their race as white, sexual and gender minority participants, and those living in low-income households. These findings are similar to other studies that showed greater exposure among sexual and gender minority youth and among older youth [4,37,50]. Previous research on the risk for SDV finds some differences between younger and older adolescents on factors that increase risk for suicide [51].…”
Section: Discussionsupporting
confidence: 89%
“…Further research could better unpack how social connections and outreach to others are being used and how that variation might explain varied impacts of support and outreach. These findings are consistent with research findings indicating that the role of social connections is complex (Mitchell et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…For example, given the complex cluster of social and economic problems that are often linked with interpersonal violence and suicide, such as poverty and marginalized social identity status, a diverse range of individual-, family-, and community-based interventions may be needed which can be informed by research. Consistent with previous studies (Banyard et al, 2021; Mitchell et al, 2021), the current research found adolescents from low-income families (a marker of low resourced communities) and those who identified as SGM were more likely to report both interpersonal violence and suicidal behavior exposure. Findings provide more evidence for our existing knowledge base about the health disparities faced by these marginalized communities.…”
Section: Discussionsupporting
confidence: 89%